Reaction Mechanisms for Chiral-Phosphate-Catalyzed Transformations Involving Cationic Intermediates and Protic Nucleophiles - Zhai, Jianyu; Reid, Jolene P. (Synlett, 2022)
Recent strategies for enantioinduction often focus on employing a chiral catalyst to noncovalently interact with the substrate. By restricting the number of low energy diastereomeric transition states the reacting components can adopt, stereoselectivity can be achieved. Many of these noncovalent interactions include a significant dispersive component and these types of contacts have historically been difficult to model accurately. Modern computational methods have been designed to overcome such limitations. Using our computational work on chiral phosphate catalysis, we discuss the reasons for enantioselectivity in diverse reaction space.1 Introduction2 Chiral Phosphate Catalysis3 Phosphate-Catalyzed Transfer Hydrogenation4 Phosphate-Catalyzed Aza-Friedel–Crafts Reaction5 Phosphate-Catalyzed Reactions Involving Allenamides6 Comprehensive Qualitative Models7 Chiral Phosphates and Thionium Intermediates8 Conclusion
Keywords: organocatalysis; enantioselectivity; chiral phosphoric acids; density functional theory; noncovalent interactions